(3GdfRgI GdSfjI aj NHGQ GdNdaGA hGdedhc GdeUQjIs - (3MSf Hf MSjf GdWhdhfi GdYeGQ GdMfajs; (3HOQ GdOjf MSf Hf MSjf Hf CMeO, GHf GdWhdhfj,J (B909 (3g` s
(3ChdgG (B:s
(3GdMeO ddg heMU GdCee heMi GdQee hHYO ajbhd GdMfai deG QCjJ HYV SGOGJfG GdYdeGA QVi Gddg Yfge CQNhG JhGQjNkG LeYhG ajgG CNHGQ GdUMGHI s
(3BNQgG (B:s
(3jfJgi HJQLeI bGfUhI GdZhQi Hbhdg (B: (3aUGQ HaVd Gddg ajg YOI bUhQ hHSJGf CNVQ hddg GdMeO Ydi eG CfYe ajg ef GdNjQGJ hjSQ s
(3HgG fXGe GdJYbjHIs
(3fSNI NRGFfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B189s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdJGQjNs